The effectiveness of group guidance using role-playing techniques in improving emotional regulation among tenth-grade students - Moh Showam; Suhendri Suhendri; Ellya Rakhmawati (SCHOULID: Indonesian Journal of School Counseling, 2026)
Emotional regulation is an important ability for adolescents in managing and expressing emotions appropriately. This study aimed to examine the effectiveness of group guidance using role-playing techniques in improving the emotional regulation of tenth-grade students. A pretest-posttest control group experimental design was employed with 16 students divided into experimental and control groups. Data were collected using a validated and reliable emotional regulation scale and analyzed using an appropriate inferential statistical test. The results showed that the experimental group's mean score increased from 70.63 to 74.63, while the control group's score increased only from 71.38 to 71.63. These findings indicate that group guidance using role-playing techniques was associated with improved emotional regulation. However, the limited sample size and single-school setting require cautious interpretation. Role-playing-based group guidance may therefore serve as an experiential approach in school counseling to support students' emotional regulation.